Perbandingan Keacakan Citra Enkripsi Algoritma AES dan Camelia Uji NPCR dan UACI - Layli Nur Hidayati; Gita Fadila Fitriana; Ipam Fuadina Adam (STMIK Budi Darma, 2021)
The need for data security arises because of the many threats made by outside parties to retrieve data and use it for personal interests. Security for medical images is carried out because medical images store patient health information data that is confidential. In this study, the image data used specifically uses radiological medical images. There are many techniques and algorithms that can be used to secure image data. This study uses the AES and Camellia algorithms which in their application use several different operating modes. To measure the quality of the encrypted image, the randomness level of the image was tested using the NPCR and UACI tests. Evaluation is used to determine the best algorithm and operating mode for encryption. Based on the measurement of image randomness on AES CBC, AES CFB, AES OFB, Camellia ECB, Camellia CBC, and Camellia OFB with NPCR values for encrypted images of 99.60%, 99.608%, 99.6093%, 99.6296%, 99.6072 %, and 99.6124%. Measurement of image randomness on AES CBC, AES CFB, AES OFB, Camellia ECB, Camellia CBC, and Camellia OFB with UACI values for encrypted images of 34.714%, 34.754%, 34.603%, 34.983%, 34.615%, and 34.707%.